Novel Genomic Regions of Fusarium Wilt Resistance in Bottle Gourd [Lagenaria siceraria (Mol.) Standl.] Discovered in Genome-Wide Association Study - Li, Yanwei; Wang, Ying; Wu, Xinyi; Wang, Jian; Wu, Xiaohua; Wang, Baogen; Lu, Zhongfu; Li, Guojing (Frontiers in Plant Science, 2021)
Fusarium wilt (FW) is a typical soil-borne disease that seriously affects the yield and fruit quality of bottle gourd. Thus, to improve resistance to FW in bottle gourd, the genetic mechanism underlying FW resistance need to be explored. In this study, we performed a genome-wide association study (GWAS) based on 5,330 single nucleotide polymorphisms (SNPs) and 89 bottle gourd accessions. GWAS results revealed a total of 10 SNPs (p≤0.01, -log10P≥2.0) significantly associated with FW resistance that were detected in at least two environments (2019DI, 2020DI, and the average across the two years); these SNPs were located on Chr. 1, 2, 3, 4, 8 and 9. Linkage disequilibrium (LD) block structure analysis predicted three potential candidate genes for FW resistance. Genes HG_GLEAN_10001030 and HG_GLEAN_10001042 were within the range of the mean LD block of the marker BGReSe_14202; gene HG_GLEAN_10011803 was 280 kb upstream of the marker BGReSe_00818. Real-time quantitative PCR (qRT-PCR) analysis showed that HG_GLEAN_10011803 was significantly up-regulated in FW-infected plants of YD-4, Yin-10, and Hanbi; HG_GLEAN_10001030 and HG_GLEAN_10001042 were specifically up-regulated in FW-infected plants of YD-4. Therefore, gene HG_GLEAN_10011803 is likely the major effect candidate gene for resistance against FW in bottle gourd. This work provides scientific evidence for the exploration of candidate gene and development of functional markers in the bottle gourd FW-resistant breeding programs.